2012
DOI: 10.1073/pnas.1201629109
|View full text |Cite
|
Sign up to set email alerts
|

Yno1p/Aim14p, a NADPH-oxidase ortholog, controls extramitochondrial reactive oxygen species generation, apoptosis, and actin cable formation in yeast

Abstract: The large protein superfamily of NADPH oxidases (NOX enzymes) is found in members of all eukaryotic kingdoms: animals, plants, fungi, and protists. The physiological functions of these NOX enzymes range from defense to specialized oxidative biosynthesis and to signaling. In filamentous fungi, NOX enzymes are involved in signaling cell differentiation, in particular in the formation of fruiting bodies. On the basis of bioinformatics analysis, until now it was believed that the genomes of unicellular fungi like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
138
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(145 citation statements)
references
References 38 publications
5
138
1
1
Order By: Relevance
“…When considered together, our results are consistent with a model whereby the M. oryzae Nox2/NoxR complex is essential for septin-mediated Factin assembly at the appressorium pore, which is a prerequisite for penetration peg formation and rice infection. In Saccharomyces cerevisiae, a recently identified Nox-encoding gene, YNO1, has also been implicated in actin cable formation (30), suggesting that regulation of F-actin dynamics may be one of the key underlying mechanisms by which Nox exert their diverse roles in cellular differentiation. In M. oryzae, Nox2 is regulated as part of a complex involving NoxR and is also known to interact with Rac1 (31), a small GTPase involved in polarized cell growth and also implicated in F-actin dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…When considered together, our results are consistent with a model whereby the M. oryzae Nox2/NoxR complex is essential for septin-mediated Factin assembly at the appressorium pore, which is a prerequisite for penetration peg formation and rice infection. In Saccharomyces cerevisiae, a recently identified Nox-encoding gene, YNO1, has also been implicated in actin cable formation (30), suggesting that regulation of F-actin dynamics may be one of the key underlying mechanisms by which Nox exert their diverse roles in cellular differentiation. In M. oryzae, Nox2 is regulated as part of a complex involving NoxR and is also known to interact with Rac1 (31), a small GTPase involved in polarized cell growth and also implicated in F-actin dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…These authors showed that Δnox1 still initated penetration peg formation but was unable to proliferate in the infected plant tissue. Furthermore, Yno1p, the NOX enzyme from yeast, has a regulatory role in actin remodeling (Rinnerthaler et al 2012). Interestingly, F-actin remodeling is also crucial for CAT fusion in N. crassa (Roca et al 2010).…”
Section: Transcriptional Profiling Reveals Differentially Regulated Gmentioning
confidence: 99%
“…The current study reveals that Cch1p responds to both fast activation (high pH and H 2 O 2 ) and slow activation stress (tunicamycin and mating pheromones) in a similar manner that parallels the redox changes observed in the cell. Indeed, these various stress responses and triggers in yeast cells have been reported to result in oxidative stress (Pozniakovsky et al, 2005;Rinnerthaler et al, 2012;Viladevall et al, 2004;Zhang et al, 2006), underlining the possibility that activation of Cch1p is a conserved redox-dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Slow activation mechanisms, like mating pheromone exposure, have also been shown to produce reactive oxygen species (ROS) in S. cerevisiae cells (Pozniakovsky et al, 2005;Zhang et al, 2006). Similarly, tunicamycin has also been shown to generate ROS in WT yeast cells (Rinnerthaler et al, 2012). Thus, it was of interest to determine whether an alteration in the redox environment of the cytosol might be causing these slow and fast activation effects, and the oxidizing state might be the common activation mechanism.…”
Section: Cch1p Activation Responds To the Redox State In The Cellmentioning
confidence: 99%